Alcohol intoxication impairs eyewitness memory and increases suggestibility: Two field studies. Issue 3 (26th May 2019) - van Oorsouw, Kim; Broers, Nick J.; Sauerland, Melanie
Summary: Two field studies tested the effect of alcohol intoxication on memory for a live interaction at immediate, delayed, and repeated testing. In Study 1 ( N  = 86), one researcher presented bar tenants with (misleading) questions regarding a preceding interaction with another researcher. One week later, participants' memory was tested again. Study 2 ( N  = 189) added a delayed‐testing only condition. We hypothesized intoxication to impair memory and enhance suggestibility and explored whether time of testing affected the outcome on these variables. In Study 1, intoxication reduced completeness and increased suggestibility. In Study 2, intoxication reduced completeness and increased suggestibility in delayed‐only and repeated testing, compared with immediate testing. Sober participants benefited from repeated testing in Study 2, but not Study 1. Findings lend support for consolidation and decay theory and suggest that immediate (intoxicated) testing is preferable over delayed‐only testing. Findings provide little support for alcohol myopia theory.